Routledge handbook of drugs and sport (Routledge, 2015)
Doping has become one of the most important and high-profile issues in contemporary sport. Shocking cases such as that of Lance Armstrong and the US Postal cycling team have exposed the complicated relationships between athletes, teams, physicians, sports governing bodies, drugs providers, and judicial systems, all locked in a constant struggle for competitive advantage. The Routledge handbook of drugs and sport is simply the most comprehensive and authoritative survey of social scientific research on this hugely important issue ever to be published. It presents an overview of key topics, problems, ideas, concepts and cases across seven thematic sections, which include chapters addressing: The history of doping in sport; Philosophical approaches to understanding doping; The development of anti-doping policy; Studies of doping in seven major sports, including athletics, cycling, baseball and soccer. In-depth analysis of four of the most prominent doping scandals in history, namely Ben Johnson, institutionalized doping in the former GDR, the 1998 Tour de France and Lance Armstrong, WADA and the national anti-doping organizations. Key contemporary debates around strict liability, the criminalization of doping, and zero tolerance versus harm reduction. Doping outside of elite sport, in gyms, the military and the police.